Pushing aggressively for political renewal - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2015)
In one of the most anticipated Cabinet reshuffles that precedes the cusp of a leadership transition, Prime Minister Lee Hsien Loong did not disappoint and kept to his word to “push aggressively” for political renewal and succession. While change amid continuity is an apt description for the new line-up, there is no doubting that the emphasis is clearly on change.